Flow cytometric analyses of somatic and pollen nuclei in midday flowers (Aizoaceae). Issue 4 (1st October 2016) - Braun, Philipp; Winkelmann, Traud
Abstract: Endoreduplication (continuous DNA replication without chromosomal or cellular division) is known to be extraordinarily pronounced in a number of succulent plants, including midday flower species. Cytological investigations in different genotypes of the Aizoaceae genera Lampranthus and Delosperma were performed with three objectives: characterization of endoreduplication in several plant organs; determination of absolute DNA contents (pg/2C); and screening for unreduced male gametes. Flow cytometric determinations of absolute DNA contents using internal standards were carried out on nuclei extracted from pollen tubes. Further analyses of pollen nuclei were intended to verify the occurrence of unreduced gametes in the two genera. In contrast to the majority of angiosperms, in which endoreduplication is often restricted to certain tissues or cell types, the investigated succulents primarily consisted of cells with elevated DNA contents. Absolute DNA contents ranged from 1.6 to 2.36 pg/2C in Lampranthus and from 1.18 to 3.68 pg/2C in Delosperma . In flow cytometric analyses of pollen nuclei, signals corresponding to 1C, 2C and 3C DNA levels were detected. Microscopic observations of sample suspensions revealed that, instead of unreduced gametes, pairs of sperm nuclei and intact male germ units (MGUs) were the primary cause for the detection of signals higher than 1C. Thus, flow cytometric pollen nuclei analysis turned out to be a valuable tool to determine cell DNA contents in endocycling plants, but entails the risk of false-positive results in screenings for unreduced gametes due to persistent nuclei associations.